Adaptive Physical Education for Children with Special Needs at Lazuardi Kamila Elementary School - Forestry, Silmi; Kristiyanto, Agus; Legowo, Edy (Journal of ICSAR, 2019)
Physical barriers, intelligence and psychic can influence the physical activity of children with special needs. Physical activity for children with special needs can be learned in an adaptive physical education. This study uses type of qualitative approach with case study research strategy. The research aims to gain an overview of the implementation of learning adaptive physical education for children with special needs in inclusive schools elementary Lazuardi Kamila. The results showedthat the adaptive physical education for special needs children in elementary Lazuardi Kamila is already well underway.